Pemahaman Alur Percakapan dalam Mata Kuliah Kaiwa dengan Menggunakan Media Story Pictures pada Mahasiswa Semester II (2012-2013) Program Studi Pendidikan Bahasa Jepang Universitas Riau - Fajriansah, Fuad; Rahayu, Nana; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aims to describe and test whether the media story pictures to enhanceunderstanding of the flow of conversation Kaiwa the second semester students (2012-2013)Japanese Language Study Program University of Riau. Learners numbering 42 people (21groups). The results of this study explains that: first, understanding the flow of conversationKaiwa can be improved by using a media story pictures. Before the use of the media, somelearners (respondent) scored below the standard. Secondly, the learners interested andmotivated. It can be seen from the test results. Third, by using of media story pictures makelearning effective and get the maximum learning.Keyword : Story Pictures Media, Conversation of Kaiwa